Marketing digital en el Hotel Grand River de la ciudad de Babahoyo. - Bajaña Flores, Luis Javier (2022)
The purpose of this research is to evaluate the effectiveness of digital marketing of the Grand River Hotel in the city of Babahoyo. This business performs advertising work from online platforms, where there are certain inconsistencies that make it impossible to capture the attention of the public and therefore, it is difficult to achieve good results when promoting the hotel offer. The development of this study has great relevance because digital marketing is a tool that brings many advantages to both companies and consumers, however it is essential to develop successful procedures to succeed in advertising, and consequently be a positive contribution to the level of sales. The descriptive methodology was useful, where information was collected from direct and indirect sources for subsequent analysis, reaching the conclusion that poor content management and little advertising reach negatively affect the effectiveness of digital marketing of the Grand River Hotel, being important that there is consistency, variety and novelty in the publications shared by the business, in order to capture the attention of users on the web and get a growing audience, which favors the tasks of promotion and advertising respectively.